Effect of bike-fit in the perception of comfort, fatigue and pain - Priego Quesada, J. I.; Pérez-Soriano, P.; Lucas-Cuevas, A. G.; Palmer, R. S.; Cibrián Ortiz de Anda, R. M. (Journal of Sports Sciences, 2014)
The aim of this study was to assess the influence of different bike positions on the perception of fatigue, pain and comfort. Twenty cyclists underwent three tests that involved cycling for 45 min at their individual 50% peak aerobic power output while adopting different positions on the bike. Participants performed the cycling tests adopting three positions defined by two parameters (knee flexion angle [20°, 30°, 40°] and trunk flexion angle [35°, 45°, 55°]) in random order. Angles were measured using a 2D motion analysis system during cycling and applying Fonda`s correction factor. Perceptions of comfort, fatigue and pain were reported before the end of each test. The combination of 40° knee flexion and 35° trunk flexion was perceived as the most uncomfortable position. Moreover, greater knee flexion had a negative effect on trunk comfort, accompanied by greater levels of fatigue and pain perception in the anterior part of the thigh and knee. In conclusion, cyclists perceived the most comfortable position to be when the saddle height was within the recommended knee angle (30° calculated from the offset position or 40 ± 4.0° of absolute value). Upright trunk was found to be the most comfortable position for recreational cyclists, where aerodynamics is not so important. Cyclists` bike perceptions should be taken into account when it comes to choosing the most beneficial position, since this can play a role in injury prevention and enhance cycling performance.